Advances in group processes. Vol. 18 - Lawler, Edward J.; Thye, Shane R.; Macy, Michael W. (Advances in group processes., 2001)
Advances in Group Processes publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. Volume 18 addresses a broad range of theoretical and empirical questions that cut across sociology, psychology, economics, and political science. The first two contributions examine the perceptual and interactional factors that result in leadership and inequality in small groups. The next chapter explores the psychology of buying and selling, focusing in particular on the perceptual biases that emerge when individuals exchange money for goods. The fourth chapter seeks to identify important personal characteristics and social factors that precipitate trust among strangers. Two chapters then address relatively new questions in the social sciences. Chapter five asks how the study of autistic individuals can shed light on basic cognitive processes and a theory of the mind. Chapter six shows how evolutionary psychology can help explain the emergence of social structures such as kinship networks. The final two chapters bring experimental evidence to bear on questions of status, influence, and affective reactions in groups. Overall, the volume includes contributions by major scholars from various social scientific disciplines that work in the general area of group processes.